Genome-wide analysis of plant miRNA action clarifies levels of regulatory dynamics across developmental contexts - Ma, Xiaoli; Denyer, Tom; Javelle, Marie; Feller, Antje; Timmermans, Marja C.P. (Genome Research, 2021)
Development of complex organisms requires the delicate and dynamic spatiotemporal regulation of gene expression. Central to this are microRNAs (miRNAs). These mobile small RNAs offer specificity in conveying positional information and versatility in patterning the outcomes of gene expression. However, the parameters that shape miRNA output during development are still to be clarified. Here, we address this question on a genome-wide scale, using the maize shoot apex as a model. We show that patterns and levels of miRNA accumulation are largely determined at the transcriptional level, but are finessed post-transcriptionally in a tissue-dependent manner. The stem cell environments of the shoot apical meristem and vasculature appear particularly liable to this. Tissue-specific effects are also apparent at the level of target repression, with target cleavage products in the vasculature exceeding those of other tissues. Our results argue against a clearance mode of regulation purely at the level of transcript cleavage, leading us to propose that transcript cleavage provides a baseline level of target repression, onto which miRNA-driven translational repression can act to toggle the mode of target regulation between clearance and rheostat. Our data show how the inherent complexities of miRNA pathways allow the accumulation and activity of these small RNAs to be tailored in space and time to bring about the gene expression versatility needed during development.